2020
DOI: 10.1371/journal.pone.0226873
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of post-transplantation diabetes mellitus incidence and risk factors between kidney and liver transplantation patients

Abstract: BackgroundMost prior studies characterizing post-transplantation diabetes mellitus (PTDM) have been limited to single-cohort, single-organ studies. This retrospective study determined PTDM across organs by comparing incidence and risk factors among 346 liver and 407 kidney transplant recipients from a single center. MethodsUnivariate and multivariate regression-based analyses were conducted to determine association of various risk factors and PTDM in the two cohorts, as well as differences in glucometrics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Although the majority of PTDM data are derived from kidney transplant recipients, PTDM incidence has been reported as being higher in other solid organs. Compared to kidney transplant recipients, whose PTDM incidence ranges between 10% and 20% [3‐5], PTDM occurs in 20% to 30% of heart transplant recipients [6], 20% to 40% of liver transplant recipients [7‐11], and 20% to 40% of lung transplant recipients [12,13] (as reviewed in [14] and shown in Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the majority of PTDM data are derived from kidney transplant recipients, PTDM incidence has been reported as being higher in other solid organs. Compared to kidney transplant recipients, whose PTDM incidence ranges between 10% and 20% [3‐5], PTDM occurs in 20% to 30% of heart transplant recipients [6], 20% to 40% of liver transplant recipients [7‐11], and 20% to 40% of lung transplant recipients [12,13] (as reviewed in [14] and shown in Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…2). It may seem that PTDM is more common among liver rather than kidney transplant recipients, as one center, which reported virtually the same immunosuppressant use in both types of solid transplant recipients, found that the incidence of PTDM was much higher in individuals receiving a liver rather than those receiving a kidney transplant (30% vs. 19%, respectively [9]). Risk factors for development of PTDM in liver transplant recipients are most often reported to be age [8], higher BMI [8,10,11], and especially hepatitis C virus (HCV) infection [7,8,10,11] as well as use of tacrolimus [7,8,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…We utilized 3 previously published datasets on kidney, liver, and heart transplantation patients [ 10 12 , 24 , 25 ]. The datasets were compiled through a de-identified chart review with IRB approval.…”
Section: Methodsmentioning
confidence: 99%
“…The kidney and liver patients were followed up at 1-, 4-, and 12-months after transplant and data were collected on the same variables as for the heart patients as well as hypoglycemic medication administered to patients at each time point after transplant. Immunosuppression protocols differed by organ and are described in previous studies on these patient populations [ 10 , 11 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation